The role of epigenetic modifications in the osteogenic differentiation of adipose-derived stem cells. (2nd November 2019) - Chen, Ruixin; Ren, Lin; Cai, Qingwei; Zou, Yang; Fu, Qiang; Ma, Yuanyuan
ABSTRACT: Over the last decade, stem cells have drawn extensive attention from scientists due to their full potential in tissue engineering, gene therapy, and cell therapy. Adipose-derived stem cells (ADSCs), which represent one type of mesenchymal stem cell (MSC), hold great promise in bone tissue engineering due to their painless collection procedure, their ability to self-renew and their multi-lineage differentiation properties. Major epigenetic mechanisms, which involve DNA methylation, histone modifications and RNA interference (RNAi), are known to represent one of the determining factors of ADSC fate and differentiation. Understanding the epigenetic modifications of ADSCs may provide a clue for improving stem cell therapy in bone repair and regeneration. The aim of this review is to present the recent advances in understanding the epigenetic mechanisms that facilitate ADSC differentiation into an osteogenic lineage, in addition to the characteristics of the main epigenetic modifications.